PEDAGOGICAL AND PSYCHOLOGICAL PRINCIPLES OF WORKING WITH STUDENTS WITH DIFFICULT EDUCATION - F. N. Rakhimova (Bright Mind Publishing, 2025)
The article mainly studies the psychological processes of a child in order to achieve cognitive, speech, emotional, willpower, as well as the development of various activities such as play, study, work and the formation of abilities, as a person. The character of children with difficult upbringing and the reasons for falling into such a difficult situation and depression are discussed. The child perceives the world and the environment through the eyes of the parents, that is, the parents are the responsible persons for the upbringing of the child.
Keywords: Child, psyche, information, theories, research, upbringing, difficult upbringing.